Video Summarization Based on Camera Motion and a Subjective Evaluation Method. (3rd June 2007) - Guironnet, M.; Pellerin, D.; Guyader, N.; Ladret, P.
Abstract : We propose an original method of video summarization based on camera motion. It consists in selecting frames according to the succession and the magnitude of camera motions. The method is based on rules to avoid temporal redundancy between the selected frames. We also develop a new subjective method to evaluate the proposed summary and to compare different summaries more generally. Subjects were asked to watch a video and to create a summary manually. From the summaries of the different subjects, an "optimal" one is built automatically and is compared to the summaries obtained by different methods. Experimental results show the efficiency of our camera motion-based summary.